The God of Process – the Interconnectedness of the World The Process Theology as A Frame for a Glocal Spirituality - Kleden, Paul Budi (JURNAL LEDALERO, 2024)
Drawing inspiration from the process theology, this article aims to develop a glocal spirituality in view of fostering an alternative perspective on the dynamics of globalization. While globalization has traditionally been understood and experienced as the homogenization of world cultures, leading to the diminishment of local cultures, I argue that it can also be perceived and lived as an opportunity for local cultures to express themselves on a global stage. Consequently, rather than being diminished, local cultures are enriched through their engagement in the dynamics of globalization through their encounter and interaction with other cultural traditions. This interaction not only enriches local cultures but also makes the global reality more pluralistic due to the contributions of diverse local cultures. In this context, globalization manifests as glocalization, an interaction between global and local contexts. However, this interaction requires a specific spirituality to sustain it. In this article, I further argue that process theology, inspired by the process philosophy of Alfred North Whitehead, could provide a framework for developing the spirituality necessary to support such glocalization dynamics.Keywords: the God of process; process theology; interconnectedness; glocal spirituality